Fortification of Yogurt with Arabica Coffee Cascara Extract: The Effects of Concentration and Fermentation Duration on Acidity and Sensory Characteristics - Muhammad Nur Kholis; Rahardian Khalid Perwira Wibowo; Yogi Pratama Yuda Laksana (Agroindustrial Technology Journal, 2026)
Coffee cascara, a by-product of coffee processing, is a potential source of bioactive compounds such as polyphenols and chlorogenic acids. However, its application in yogurt fermentation systems remains limited. Therefore, this study aimed to evaluate the effect of cascara extract concentration and fermentation time on the physicochemical and sensory properties of yogurt. This study aimed to evaluate the effect of Arabica coffee cascara extract concentration (water-based) and fermentation duration on the acidity characteristics and sensory acceptance of yogurt. The experiment was conducted using a factorial completely randomized design with two factors: cascara extract concentration (1.5%, 2%, and 2.5% w/v) and fermentation duration (3 and 6 hours). The evaluated parameters included pH, titratable acidity (TA), and sensory attributes (color, aroma, taste, and overall acceptance) assessed using a hedonic test with untrained panellists The results demonstrated that fermentation duration significantly influenced yogurt acidification, resulting in lower pH values and higher titratable acidity as fermentation duration increased. The pH values ranged from 4.63 to 4.92, while titratable acidity ranged from 0.58% to 0.75% lactic acid. The addition of cascara extracts up to 2.5% did not inhibit the metabolic activity of lactic acid bacteria during fermentation. Sensory evaluation indicated that yogurt containing 2% cascara extract fermented for 6 hours obtained the highest overall acceptance score, indicating an optimal balance between acidity and sensory characteristics. These findings demonstrated that Arabica coffee cascara extract has potential as a functional ingredient in yogurt production while supporting the valorization of coffee processing by-products into value-added fermented dairy products.